EFEKTIVITAS PENETAPAN STATUS HUKUM PENGANGKATAN ANAK DI KOTA PAREPARE - Sitti Faisyah Az Zahra Darwis; Agus Muchsin; Aris Aris; Fikri Fikri; Mukhtar Mukhtar (Jurnal AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2026)
Child adoption is a form of child protection regulated under Indonesian positive law. However, adoption practices in Parepare City are still predominantly carried out through Bugis-Makassar customary mechanisms based on family agreements without formal legal procedures. This practice may create uncertainty regarding the legal status of adopted children, particularly in matters of inheritance, civil registration, and child rights protection. This study aims to analyze the effectiveness of legal status determination in child adoption and identify the factors influencing its implementation in Parepare City. Employing a normative juridical approach and library research method, the study analyzes statutory regulations, legal literature, and the socio-cultural context of the Bugis-Makassar community. The findings indicate that the effectiveness of legal status determination for child adoption remains low. The main obstacles include procedural complexity, limited public awareness, high administrative costs, and the strong influence of customary norms that are often prioritized over state law. These conditions reflect a gap between legal substance and legal culture. The study proposes the Customary-Legal Harmonization-Based Adoption Model (MPAHA), which emphasizes procedural simplification, financial support, collaborative legal awareness programs, and strengthened post-adoption supervision. This model is expected to enhance legal certainty while preserving the familial values of the Parepare community.